A method study on the value chain optimisation of tourism industry based on big data. (2017) - Wang, Yinghua
The increased demand promotes the development of tourism industry, big data has brought new method for the tourism industry to update value chain and raise industrial development. In this paper, we clarify the definition and characteristics of big data, talking about shaping and upgrading the tourism industry value chain. The internal and external value chain of tourism industry under big data is analysed. Then we put forward the method construction and development countermeasures of tourism industry based on big data.